Assessing perceived and functional health literacy among parents in Cyprus: A cross-sectional study - Menikou, Joanna; Middleton, Nicos; Papastavrou, Evridiki; Nicolaou, Christiana (My University, 2023)
Parents often must take decisions regarding their children's health, which requires certain skills and competences. Parental health literacy (HL) is important in establishing positive health-promoting behaviours and better health outcomes to their children. Limited parental HL has been associated with various negative children's health outcomes. The aim of the study was to explore perceived and functional HL among parents in Cyprus.
Keywords: Child; Cross-Sectional Studies; Cyprus; Female; Health Literacy; Humans; Parents; Surveys and Questionnaires